2017
DOI: 10.24966/ggm-8662/100015
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related-Changes-of-Trace-Element-Contents-in-Intact-Thyroid-of-Females-Investigated-by-Neutron-Activation-Analysis

Abstract: IntroductionThe endocrine organs, including the thyroid gland, undergo important functional changes during aging and a prevalence of thyroid dysfunction is higher in the elderly as compared to the younger population [1,2]. Advancing age is known to influence the formation of adenomatous goiter and thyroid cancer [3]. The prevalence of thyroid nodules is increased in the elderly, reaching a frequency of nearly 50% by the age of 65 [4]. Both prevalence and aggressiveness of thyroid cancer increase with age [2]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(76 citation statements)
references
References 22 publications
(25 reference statements)
12
64
0
Order By: Relevance
“…In our previous study a significant positive correlation between age and some chemical element contents in the thyroid was observed [23][24][25][26][27][28]. It was concluded that an age-dependent excess of intra-thyroidal I and zinc (Zn) concentration are probably one of the factors acting in both initiation and promotion stages of thyroid carcinogenesis [9,24,25], as it was earlier shown by us for I in thyroid and for Zn in prostate gland [29][30][31][32][33][34]. Moreover, it seems fair to suppose that besides I and Zn, many other chemical elements also play a role in the pathophysiology of the thyroid.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our previous study a significant positive correlation between age and some chemical element contents in the thyroid was observed [23][24][25][26][27][28]. It was concluded that an age-dependent excess of intra-thyroidal I and zinc (Zn) concentration are probably one of the factors acting in both initiation and promotion stages of thyroid carcinogenesis [9,24,25], as it was earlier shown by us for I in thyroid and for Zn in prostate gland [29][30][31][32][33][34]. Moreover, it seems fair to suppose that besides I and Zn, many other chemical elements also play a role in the pathophysiology of the thyroid.…”
Section: Introductionmentioning
confidence: 80%
“…The content of Br, Ca, Cl, I, K, Mg, Mn, and Na were determined by INAA-SLR using a horizontal channel equipped with the pneumatic rabbit system of the WWR-c research nuclear reactor (Branch of Karpov Institute, Obninsk). Details of used neutron flux, nuclear reactions, radionuclides, gamma-energies, and spectrometric unit were presented in our earlier publications concerning the INAA-SLR chemical element contents in human thyroid, scalp hair, and prostate [7,23,27,40] In a few days after INAA-SLR all thyroid samples were repacked separately in a high-purity aluminum foil washed with rectified alcohol beforehand and placed in a nitric acid-washed quartz ampoule and used for INAA-LLR. A vertical channel of the WWR-c research nuclear reactor (Branch of Karpov Institute, Obninsk).was applied to determine the content of Ag, Co, Cr, Fe, Hg, Rb, Sb, Sc, Se, and Zn by INAA-LLR.…”
Section: Introductionmentioning
confidence: 99%
“…An overload of Rb could modulate proliferative responses of the cell, as was shown for bone marrow leukocytes [19]. In our previous studies it was found a significant age-related increase of Rb content in female thyroid [23,[26][27][28]. Therefore, a goitrogenic and, probably, carcinogenic effect of excessive Rb level in the thyroid of old females was assumed.…”
Section: Effect Of Malignant Transformation On Chemical Element Contementioning
confidence: 99%
“…In our previous studies it was found a significant age-related increase of Br content in human thyroid [23,[26][27][28]. Therefore, a goitrogenic and, probably, carcinogenic effect of excessive Br level in the thyroid of old females was assumed.…”
Section: Effect Of Malignant Transformation On Chemical Element Contementioning
confidence: 99%
See 1 more Smart Citation